A study of hedging devices in conversations in Gone with the wind by Margaret Mitchell. M.A Thesis Linguistics: 60 22 15 - Nguyễn, Thị Thanh Huyền (University of Languages and International Studies, 2017)
The objectives of the research were to investigate the linguistic devices of hedges and major pragmatic functions of identified hedges in the conversations in the novel of Gone with the Wind by Margaret Mitchell. Two levels of linguistic descriptions – the (...)